The Serine Protease HTRA-1 Is a Biomarker for ROP and Mediates Retinal Neovascularization - Owen, Leah A.; Shirer, Kinsey; Collazo, Samuel A.; Szczotka, Kathryn; Baker, Shawna; Wood, Blair; Carroll, Lara; Haaland, Benjamin; Iwata, Takeshi; Katikaneni, Lakshmi D.; DeAngelis, Margaret M. (Frontiers in Molecular Neuroscience, 2020)
Retinopathy of prematurity (ROP) is a blinding aberrancy of retinal vascular maturation in preterm infants. Despite delayed onset after preterm birth, representing a window for therapeutic intervention, we cannot prevent or cure ROP blindness. A natural form of ROP protection exists in the setting of early-onset maternal preeclampsia, though is not well characterized. As ischemia is central feature in both ROP and preeclampsia, we hypothesized that angiogenesis mediators may underlie this protection. To test our hypothesis we analyzed peripheral blood expression of candidate proteins with suggested roles in preeclamptic and ROP pathophysiology and with a proposed angiogenesis function [HTRA-1, IGF-1, TGFβ-1 and VEGF-A]. Analysis in a discovery cohort of forty maternal infant pairs found that elevated HTRA-1 (high-temperature requirement-A serine peptidase-1) was significantly associated with increased risk of ROP and the absence of preeclampsia, thus fitting a model of preeclampsia-mediated ROP protection. We validated these findings and further demonstrated a dose response between systemic infant HTRA-1 expression and risk for ROP development in a larger and more diverse validation cohort consisting of preterm infants recruited from two institutions. Functional analysis in the oxygen induced retinopathy (OIR) murine model of ROP supported our systemic human findings at the local tissue level, demonstrating that HtrA-1 expression is elevated in both the neurosensory retina and retinal pigment epithelium by RT-PCR in the ROP disease state. Finally, transgenic mice over-expressing HtrA-1 demonstrate greater ROP disease severity in this model. Thus, HTRA-1 may underlie ROP protection in preeclampsia and represent an avenue for disease prevention, which does not currently exist.